COVID-19 Impact on Concrete Producers: Conflict, Stress, Compensation, and Work: Dampak Konflik Kerja, Stres Kerja, dan Kompensasi pada Kinerja Karyawan Produsen Beton Selama Pandemi Covid-19 - Muhammad Dedy Agung Syaiful Rahman; Mas Oetarjo (Universitas Muhammadiyah Sidoarjo, 2022)
The COVID-19 pandemic has profoundly affected various aspects of life, necessitating focused efforts to address its associated challenges. This quantitative study aims to investigate the impact of work conflict, job stress, and compensation on employee job satisfaction. With a population of 350 respondents, a sample size of 78 employees was randomly selected. Using multiple linear regression analysis with SPSS version 25, the results indicate that work conflict, job stress, and compensation collectively influence employee job satisfaction. Individually, work conflict negatively and significantly impacts job satisfaction, while job stress and compensation positively and significantly influence job satisfaction. These findings emphasize the importance of addressing these factors to enhance employee job satisfaction amidst the COVID-19 pandemic, with implications for organizations and policymakers alike. Highlights: The COVID-19 pandemic's impact on concrete producers' workforce, focusing on work conflict, work stress, and compensation. Quantitative study with a sample size of 78 employees, utilizing multiple linear regression analysis. Findings reveal the significant influence of work conflict, work stress, and compensation on employee work satisfaction during the pandemic. Keywords: Work Conflict, Work Stress, Compensation, Employee Work, Concrete Producers